COMPARISON ANALYSIS OF CUSTOMER PERCEIVED VALUES BETWEEN HONDA MOBILIO AND SUZUKI ERTIGA IN MANADO CITY - Koagow, Rendy Rezza (Universitas Sam Ratulangi, 2015)
The rapid development of automotive industry in Indonesia has caused tight level of competition, especially in automobile industry, The number of products which have the same form, usability, and other features have made consumers it difficult to distinguish the products. The purpose of this research is to know the difference between the costumer perceived value of Honda Mobilio and Suzuki Ertiga. This research is comparative research that is aimed to describe the difference between Honda Mobilio and Suzuki Ertiga, using quantitative method. The result shows that Homogeneity of Consumer Perceived Value based on Usefulness is homogeneous but for Costumer Perceived Value based on Quality and based on price are not homogeneous. Company should care about the Consumer Perceived Value Based on Usefulness, Quality and Price Concept because this variables can change Consumer Perception and make differences between the product. Â Keywords: consumer perceived value, usefulness, quality, price